Investigating the chromatic contribution to recognition of facial expression. (April 2017) - Fotios, S; Castleton, H; Cheal, C; Yang, B
A pedestrian may judge the intentions of another person by their facial expression amongst other cues and aiding such evaluation after dark is one aim of road lighting. Previous studies give mixed conclusions as to whether lamp spectrum affects the ability to make such judgements. An experiment was carried out using conditions better resembling those of pedestrian behaviour, using as targets photographs of actors portraying facial expressions corresponding to the six universally recognised emotions. Responses were sought using a forced-choice procedure, under two types of lamp and with colour and grey scale photographs. Neither lamp type nor image colour was suggested to have a significant effect on the frequency with which the emotion conveyed by facial expression was correctly identified.